Thermal degradation behaviour of poly[(2-hydroxy-3-phenoxy)propyl methacrylate] and poly[(2-hydroxy-3-tetrahydrofurfuryloxy)propyl methacrylate] - Coskun, M; Temüz, MM; Koca, M (Elsevier Sci Ltd, 2003)
(2-Hydroxy-3-phenoxy)propyl methacrylate (PPMA) and (2-hydroxy-3-tetrahydrofurfuryloxy)propyl methacrylate (THPMA) were polymerised using benzoyl peroxide as initiator in 1,4-dioxane at 60 degreesC. The polymers were characterized by gel permeation chromatography (GPC), differential scanning calorimetry (DSC), IR, H-1 and C-13 NMR techniques. The thermal degradations of poly(THPMA) and poly(PPMA) were investigated by thermogravimetric analysis (TGA) and programmed heating of the polymers from ambient to 500 degreesC under vacuum, followed by product collection, and using IR spectra of partially degraded polymer. IR, GC-MS, H-1 and C-13 NMR techniques were used in product identification studies. Although the heating of poly(THPMA) to 330 degreesC gives the monomer in ratio 87.0%, it gives the monomer in ratio 47.7% between 330 and 500 degreesC, whereas poly(PPMA) gives the monomer in ratio 85.9% during heating from ambient to 500 degreesC. Activation energies of the degradations given the corresponding monomers in ratio 85% at least, and the mechanism of degradation given some other major products, are discussed. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: methacrylate; hydroxy and alkoxy (phenoxy) side chain; thermal degradation